(untitled) (Bangladesh Journal of Medical Science, 2013)
Objective: The study was aimed at investigating the hypoglycemic, antioxidant and Hepatoprotective effects of Chrysophyllum albidum in diabetes induced male Wistar rats. Methods: Ethanol root bark extract was administered to thirty rats of six groups A, B, C, D, E and F of five rats each, weighing between 150-170g. Diabetes was induced in Groups B, C, D, E and F using a single intraperitoneal injection of 140mg/kg of Alloxan after an overnight fast. Group A served as the normal control while Group B served as the diabetic control. Group C had metformin of 500mg while Groups D, E and F received 50, 100 and 200mg/kg / bw/ day of the plant extract respectively through orogastric intubation. All the animals were given normal rat chow and water freely. Blood glucose level was determined and the experiment lasted for 3 weeks. On day 21 after an overnight fast, animal were anaesthetized and blood samples were collected by cardiac puncture under inhaled chloroform for the determination of superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) assays. The liver function test, ALT, AST and ALP was determined. Result: This showed that C. albidum and metformin significantly (p < 0.05) lowered the Fasting blood glucose (FBS), the activities of SOD and CAT was dose- dependently increase when compared to the diabetic control and there was also a reduction of MDA in the treated groups. There was decrease in the activity of ALT, AST and ALP, which was also dose-dependent. Conclusion: The results showed that the plant has significant antidiabetic activity and could therefore be employed for the treatment of diabetes mellitus in which free radicals are implicated. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 298-304 DOI: http://dx.doi.org/10.3329/bjms.v12i3.12721